2019
DOI: 10.1007/s10896-019-00124-5
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Parenting Behaviors: The Mediating Role of Emotion Regulation

Abstract: Maternal trauma has been linked with problematic parenting, including both harsh and permissive behaviors. However, little is known about mechanisms accounting for this association. The current study examined the potential impact of posttraumatic stress disorder (PTSD) and emotion regulation on dysfunctional parenting behaviors in a sample of community mothers. We hypothesized a mediation model wherein PTSD would be associated with dysfunctional parenting (i.e., lax and overreactive behaviors) indirectly throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Our results echo evidence that emotion regulation difficulties exacerbate trauma symptoms for this population (Kumar et al, 2019 ; Samuelson et al, 2017 ), as seen by consistently stronger correlations between coping and difficulties with emotion regulation among caregivers relative to their noncaregiving counterparts. The emotion regulation factor for difficulties with impulsive responses to stress was consistently among the strongest unique associations with all types of posttraumatic stress for both groups, with stronger effects noted among caregivers.…”
Section: Discussionsupporting
confidence: 88%
“…Our results echo evidence that emotion regulation difficulties exacerbate trauma symptoms for this population (Kumar et al, 2019 ; Samuelson et al, 2017 ), as seen by consistently stronger correlations between coping and difficulties with emotion regulation among caregivers relative to their noncaregiving counterparts. The emotion regulation factor for difficulties with impulsive responses to stress was consistently among the strongest unique associations with all types of posttraumatic stress for both groups, with stronger effects noted among caregivers.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with several studies that showed the significant effect of mothers' functioning on their children’s maladjustment in the context of exposure to continuous political and war-related violence (e.g., Pat-Horenczyk et al, 2020). Ongoing exposure to trauma and the subsequent maternal PTSD symptoms may disrupt caregiving patterns (Levy et al, 2019), affect mothers' emotion regulation, undermine effective parenting (Kumar et al, 2020), and have implications on children's prosocial (Levy et al, 2019) and self-regulation abilities (Pat-Horenczyk et al, 2020). Children may not only be affected by direct exposure to trauma, but by their mothers' response to it as well (Chemtob et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although parents' and caregivers' responsive care can play a critical role in mitigating the negative effects and destructive outcomes resulting from prolonged exposure to security threats (Lambert et al, 2014), their ability to do so is affected by their own difficulties, and depends on their ability to regulate their own emotions first, before soothing and supporting their child (Pat-Horenczyk et al,, 2020). Struggling with PTSD can affect mothers' emotion regulation, and undermine their effective parenting (Kumar et al, 2020)-resulting in children's dysregulation, emotional disorders, and behavior problems (Pat-Horenczyk et al, 2020).…”
Section: Maternal Posttraumatic Symptomatologymentioning
confidence: 99%
“…Fourth, PTSD symptoms may lead to deficits in maternal emotion regulation (Kumar et al, 2020 ), which makes it difficult to parent assertively and adequately, and may lead to a less positive and affectionate mother-child relationship (Van Ee et al, 2016 ), and harsher parenting (Ammerman et al, 2012 ), increasing the risk for child maltreatment (Banyard et al, 2003 ). Consequently, adequate recognition and referral to treatment of PTSD symptoms may enhance the effects of programs to prevent child maltreatment (Ammerman et al, 2012 ).…”
mentioning
confidence: 99%